2012
DOI: 10.17221/5917-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and immunohistochemical studies on rare cases of primary extragenital transmissible venereal tumours in the mammary gland

Abstract: Transmissible venereal tumours (TVT) are normally seen on the genitalia of both male and female dogs, and at times may be observed on extra-genital sites such as lips, oral mucosa, and peritoneum, or in organs such as the tonsils, eye, liver, spleen, kidney, lung, and musculature. The present communication deals with two rare cases of primary extragenital TVT involving the mammary glands of dogs and their pathology and immunohistochemistry. The study indicated that apart from routinely used markers such as vim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…In our study, we preferred the mutant p53 gene compared to the normal p53 gene due to its long half -life. In accordance with previous literature data, we detected p53 immunoreactivity in the cytoplasm and nucleus of tumoral cells (Coskan et al, 2011;Gupta and Sood, 2012;Gerardi et al, 2014). Stockmann et al2011b reported that they encountered a p53 positive reaction at all stages, regardless of the stage of development of the tumor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, we preferred the mutant p53 gene compared to the normal p53 gene due to its long half -life. In accordance with previous literature data, we detected p53 immunoreactivity in the cytoplasm and nucleus of tumoral cells (Coskan et al, 2011;Gupta and Sood, 2012;Gerardi et al, 2014). Stockmann et al2011b reported that they encountered a p53 positive reaction at all stages, regardless of the stage of development of the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies (Chu et al, 2001;Tiwari et al, 2016) we detected PCNA expression at a statistically higher rate in TVT cases at the progression stage compared to regression and stable stage cases. The PCNA reaction was in the nucleus of the tumoral cells and moderate to severe in accordance with the literature data (Gupta and Sood, 2012;Lokesh et al, 2014;Tiwari et al, 2016;Paramjeet et al, 2019). According to the results of our study, we thought that PCNA is a very reliable marker in determining tumor aggression and prognosis in TVT cases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a retrospective study of 29 cases Rogers et al (1998) found 2 cases with primary extragenital TVT in the nasal cavity with metastasis to the cervical lymphnodes and subcutaneous tissue in 1 dog [4]. Recently, Gupta and Sood reported primary TVT of the mammary glands without evidence of TVT in the external genitalia in 2 dogs from India [17]. Although the external genitalia are the most commonly affected by TVT, metastasis is rarely seen in internal genital organs.…”
Section: Discussionmentioning
confidence: 99%